Electrochemical Properties of Phospholipid Monolayers at Liquid-Liquid Interfaces - Hélder A. Santos (2010)
Biomembrane models built at the interface between two immiscible electrolytes (ITIES) are useful systems to study phenomena of biological relevance by means of their electrochemical processes. The unique properties of ITIES allow one either to control or measure the potential difference across the biomimetic membranes. Herein we focus on phospholipid monolayers adsorbed at liquid-liquid interfaces, and besides discussing recent developments on the subject, we describe electrochemical techniques that can be used to get insight on the interfacial processes and electrostatic properties of phospholipid membranes at the ITIES. In particular, we examine the electrochemical and physicochemical properties of (modified) phospholipid monolayers and their interaction with other biologically relevant compounds. The use of liquid-liquid electrochemistry as a powerful tool to characterize drug properties is outlined. Although this review is not a survey of all the work in the field, it provides a comprehensive referencing to current research.